Network News - Quebec Community Groups Network (QCGN) (2023)
Number of pages: 9
Keywords: Official Language Minority Community (OLMC)

Community Vitality & Acceptability of English Canadian Migrants Rated by Québecois Francophone, Acadian and Franco-Ontarian University Students - Bourhis, Richard Y.; Sioufi, Rana; Allard, Réal (2023)

A Snapshot of Poverty Among Québec’s English-speaking Communities - Provincial Employment Roundtable (PERT) (2023)
Québec is home to more than 1.2 million English speakers, representing 14.9% of the province’s population. Data from the 2021 Census of Canada indicates that English-speaking Quebecers occupy a more precarious economic position than their French-speaking counterparts, experiencing higher rates of poverty and unemployment and earning lower median incomes. Research conducted by PERT has highlighted some of the specific barriers and challenges English speakers face regarding labour market integration and retention in Québec, including lack of French-language training for the workforce, lack of English-language employability services, lack of English-language vocational training, and lack of wrap-around support services. These employment challenges impact English speakers' labour market outcomes and are associated with higher rates of poverty. Furthermore, many of these challenges, especially lack of wrap-around supports (e.g. housing or food security), can directly contribute to – and result from – poverty.

Resolution 2023-08 : Accomodate Immigrant and Refugee Children - Quebec Federation of Home and School Associations (QFHSA) (2023)
Parallel title : Resolutions Adopted at the 2023 Annual General Meeting